Analysis of Signaling Pathways of Necroptotic and Pyroptotic Cell Death in the Hearts of Rats With Type 2 Diabetes Mellitus - Horváth, C; Jarabicová, I; Rajtík, T; Bartošová, L; Ferenczyová, K; Kaločayová, B; Barteková, M; Szobi, A; Adameová, A (Physiological research, 2023)
Diabetes mellitus is known to produce various cell-damaging events and thereby underlie heart dysfunction and remodeling. However, very little is known about its inflammation-associated pathomechanisms due to necrosis-like cell death. For this purpose, we aimed to investigate signaling pathways of necroptosis and pyroptosis, known to produce plasma membrane rupture with the resultant promotion of inflammation. One-year old Zucker diabetic fatty (ZDF) rats did not exhibit significant heart dysfunction as revealed by echocardiographic measurement. On the other hand, there was a decrease in heart rate due to diabetes. Immunoblotting analysis showed that the left ventricles of ZDF rats overexpress neither the main necroptotic proteins including receptor-interacting protein kinase 3 (RIP3) and mixed lineage domain kinase-like pseudokinase (MLKL), nor the pyroptotic regulators including NLR family pyrin domain containing 3 protein (NLRP3), caspase-1, interleukin-1 beta (IL-1beta and the N-terminal gasdermin D (GSDMD-N). On the other hand, the increased activation of the RIP3 kinase due to phosphorylation was found in such hearts. In summary, we showed for the first time that the activation of cardiac RIP3 is upregulated due to disturbances in glucose metabolism which, however, did not proceed to necrosis-like cell death. These data can indicate that the activated RIP3 might also underlie other pleiotropic, non-necroptotic signaling pathways under basal conditions.
Keywords: apoptóza; potkani Zucker; Apoptosis; Rats, Zucker; krysa rodu Rattus; Signal Transduction; Inflammation; proteinkinasy; Necrosis; Protein Kinases; nekróza; signální transdukce; zánět; Pyroptosis; diabetes mellitus 2. typu; Diabetes Mellitus, Type 2; pyroptóza; zvířata; Rats; Animals